How does habitat selection by brown bear (Ursus arctos) during the berry season change due to forestry and human disturbance - Jonsson, Jeanette (2022)
Brown bear (Ursus arctos) is the most widespread large carnivore. It is an apex predator and does not have natural enemies but is hunted by humans in Sweden. During the period July to October their main food resource is bilberry, which contains carbohydrates that are important for their fat resources before entering hibernation. In Sweden, brown bears occur in both managed and non-managed forests, some management practices such as clear-cut have a large impact on the bilberry occurrence. This study looked at how brown bears changed their diurnal habitat selection before, after, and during the bear hunt. Furthermore, I studied how forest management affects bears habitat selection with bilberry as an index. I had position data for 106 female brown bears, the study area was placed in mid-central Sweden, and I used forest information such as age, thinning year, and habitat classes. I fitted an iSSF (integrated step selection function) to analyze brown bear habitat selection. I found that there was a difference between their habitat selection due to human presence and forestry in the different periods, be-fore, during, and after the hunt. During the day there was no difference in habitat use between the three periods except for before hunt during the day were the bears selected for deciduous forests over pine. During the night there was a difference for the forests that had been clear-cut for 6-30 years ago, for all periods. These changes could be due to human presence during the day, result-ing in bears selected for these areas during the night becoming more nocturnal. Thinning of the forest influenced the habitat selection of brown bears, during the hunt bears selected thinned forest over pine during the night, but less before the hunt during the day and after the hunt both day and night. Clear-cuts influenced the bear habitat selection and differed between the periods and whether it was day or night. The most common difference compared to pine was that those areas that had been clear-cut were used less than pine, except during the hunt during the night and after the hunt during the night where they were selected more in comparison.